Taqwa in the Perspective of the Qur'an and Its Role in Islamic Counseling Therapy - Rizal, Masri; Irman, Irman (State Islamic Institute of Palopo, 2025)
This study explores the multidimensional concept of taqwa in the Qur’anic perspective and examines its relevance to Islamic counseling therapy through a systematic literature review (SLR). In response to the growing demand for spiritually integrated mental health interventions, this research synthesizes empirical and theoretical studies published between 2020 and 2025, focusing on the psychological functions of taqwa and its applicability in therapeutic settings. Using a structured search strategy across major academic databases, twenty-one articles met the inclusion criteria and were analyzed narratively based on thematic patterns. The results show that taqwa is consistently defined as a comprehensive form of spiritual awareness encompassing self-regulation, moral sensitivity, and behavioral discipline grounded in one’s relationship with God. Empirical findings indicate that taqwa-based interventions—such as dhikr, reflection on Qur’anic verses, and spiritual exercises—significantly reduce anxiety and depression, enhance emotional intelligence, strengthen resilience, and improve overall psychological well-being. Studies employing experimental and qualitative designs provide converging evidence that the internalization of taqwa can function as a therapeutic mechanism that stabilizes emotions, shapes coping strategies, and fosters spiritual-psychological balance. The review also reveals a gap between theoretical insights and practical implementation, suggesting the need for standardized counseling modules grounded in Qur’anic concepts of taqwa. This study contributes to the development of an integrated framework for Islamic counseling, demonstrating that taqwa can serve as a core psychological construct with meaningful implications for mental health practice. Future research is encouraged to expand clinical trials, develop standardized measurement tools for taqwa, and examine its effectiveness in diverse cultural and clinical settings.